Advocating university undergraduate students on implementing FCTC Article 5.3 - Kandeepan, ‪Saduri; Perera, K.M.N.; Wijesuriya, ‪Hiruni; Perera, C.S.; Rajasuriya, Mahesh (European Publishing, 2021)
Introduction: Tobacco industry uses aggressive strategies to use to make people want to buy their products, especially youths. Therefore It is needed to enhance the knowledge about industry tactics among the youngsters. Objectives: Establishment of network with university undergraduates to combat tobacco industry interferences in public health in Sri Lanka. Methods: Centre for Combating Tobacco (CCT) organized a series of advocacy sessions on Tobacco Industry Impact on Public Health and Framework Convention on Tobacco Control (FCTC) Article 5.3 targeting the university undergraduates in Sri Lanka. The first session was held on 23rd June 2019. It was organized by a group of undergraduates currently working as volunteers with CCT to empower their peers in state university science stream faculties of the Western Province. In this session Industry’s impact on substance use and public health and direct and indirect promotion strategies, Tobacco industry interference in Sri Lanka, FCTC Article 5.3 and current activities by CCT to monitor tobacco industry interference on public health and implementation of FCTC Article 5.3 in Sri Lanka were discussed. Networking and establishment of action committees to support CCT activities with university undergraduate students were discussed. Results: Opportunities for best practice strategies for tobacco interference control were identified. Policy adherence and enforcement was improved to raising the awareness with students. Conclusion(s): A majority of students supported the advocacy programme. A Network with university students was formed to combat the tobacco industry interference.
Keywords: strategies; tobacco industry interference; network